Characterization of Lactobacillus as probiotic from human intestine - Fakery, Saad S. (University of Thi-Qar Journal of Science, 2014)
In order to perform a selective isolation of bacteria tightly bound to the human gut, ileal biopsies of healthyvolunteers were treated to wash out the mucus layer and loosely bound bacterial cells. Rod-shaped, anaerobic bacteria that had remained attached to the epithelial cells were isolated and identified at the species level by biochemical tests.One isolate was identified as Bifidobacterium breve, while all the others were Lactobacilli of only two species,Lactobacilus mucosae and L. gasseri. Members of these species were found previously along with many others inintestinal samples but their predominance among bacteria strictly associated to the epithelium, as shown here, was not suspected before and suggested that these species may represent a specific sub-population of tissue-bound bacteria. A series of physiological tests was performed and indicated that all isolates were able to produce antimicrobial activity against selected pathogens and survive simulated gastric conditions. All isolates were able to grow and produce biofilm in intestinal fluid after exposure to gastric conditions. Those isolates can be proposed as potential probiotic strains for human use.